DESAIN DAN SIMULASI PEMOTONGAN WIRE CUT DIES PRESS TOOL OUTSIDE DIAMETER MICROMETER SPANNER - Agus Dani (INFO-TEKNIK, 2018)
Micrometer spanner is a tool that calibrate the micrometer in order to provide precise measurement results. Size of micrometer spanner is relatively small, making it easy lose and easily damaged. Micrometer calibration performed with improper equipment will cause the micrometer not to be precise. This research aims to obtain dies design and simulation process of making dies press tool micrometer spanner by using CAD CAM software. The results of the study are presstool dies design, simulation of wire cut process and G Code of CNC wire cut.